Understanding Buying Behavior among the Smartphone Users in Nepal - Vaidya, Rashesh; Gelal, Saraswoti (INTELLIGENCE Journal of Multidisciplinary Research, 2025)
Smartphones have seamlessly integrated into daily life for the people of Nepal, making their importance undeniable. However, the country's reliance on imports for smartphone consumption underscores the need to understand user preferences better. This paper investigates the buying behavior of smartphone users in Nepal, based on a sample of 235 randomly selected individuals from Banepa Municipality. Utilizing a five-point Likert scale, we collected valuable insights from the participants. The results reveal that user behavior is significantly influenced by reviews and recommendations, along with the specific features of smartphones. Conversely, product, price, place (distribution), and promotion attributes appear to have little effect on purchase decisions. Ultimately, when it comes to smartphones, features are paramount. Therefore, effective marketing strategies should emphasize key aspects such as speed, performance, battery life, camera capabilities, aesthetic design, and exchange options to attract Nepalese users.